A Paratextual Semiotic Reading Of Aissa Cheriet’s La Rocade - Souici , Nacera; Senoussi, Mohammed (El Omda in Linguistics and Discourse Analysis, 2024)
This research paper delves into the complex paratextual elements and the profound symbolism within the novel La Rocade (2004) by Aissa Cheriet. It explores how genre categorisation, thresholds, title and cover art serve as gateways to the text, setting expectations and shaping the reader’s engagement with the text connecting him to the historical and cultural realities rooted in the narrative. The paper further analyses the novel’s characters, who represent a microcosm of Algerian society symbolising societal decay and political upheaval. This paper presents the selected novel as a literary work that amalgamates personal narratives with the historical and political fabric of Algeria, inviting readers to reflect on the past’s influence on the present and future.